The importance of pharmaceutical assistance to patients using drugs for Covid-19: an integrative review (Research, Society and Development, 2022)
Introduction: Currently, no drug has yet been shown to be effective for its treatment of Covid-19, and although there are no clinical trial data that support any prophylactic treatment, in addition to vaccines, other off-label drugs are being used. In this scope, pharmaceutical care is included, understood as a set of actions aimed at the promotion, protection and recovery of health, both individual and collective. Objective: To present an integrative review on the efficiency of pharmaceutical care in relation to the potential risks of the indiscriminate use of medicines in the Covid-19 pandemic. Materials and methods: Data collection took place between 2017 and 2022, through the following databases: Scientific Electronic Library Online (SCIELO), Google Scholar, and LILACS - Bireme (Latin American and Caribbean Literature in Health Sciences). Results: Through the search carried out from the databases described, a total of 11 articles were found from the descriptors and search criteria applied to the research. Discussion: The pharmacist is a health promoter, guides the patient on the rational use of medicines in this time of the Covid-19 pandemic. It is up to this professional to monitor the triage of patients, calm and guide, in order to avoid overcrowding the health system. Conclusion: We present an analysis to be used in future studies on the subject, since it is up to the pharmacist, the last link between the medication and the patient, to guide and prevent self-medication in Covid-19.